Atrial fibrillation and 13-year risk of CVD mortality in Russian population cohort. (11th May 2022) - Shapkina, M; Ryabikov, A; Mazdorova, E; Titarenko, A; Avdeeva, E; Scherbakova, L; Pikhart, H; Bobak, M; Malyutina, S
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): The study was supported by RFBR #20-313-90015, RAS # АААА-А17-117112850280-2 Introduction: Given the worldwide increase in life expectancy, ageing-related conditions are becoming increasingly important. Atrial fibrillation (AF) is the most common arrhythmia and a serious predictor of the progression of heart failure and thromboembolic events (largely, stroke). Thus, the study of AF impact on cardiovascular (CVD) mortality is of particular relevance. Objectives: We aimed to analyze the impact of AF on the 13-year risk of CVD mortality in the Russian population sample of elderly age. Methods: A random population sample (n=9360, age 45-69 years) was examined at baseline in 2003-2005 in the Russian arm of the HAPIEE project. The cohort was re-examined twice and was followed up for end points up to end of 2017 (12.7 years on the average). Fatal end-points were ascertained by local mortality register; the current study focused on CVD deaths. Baseline AF was defined by rest ECG with evaluation by the Minnesota code (MC 8-3-1, 8-3-2; 6-8 with "fibrillation" for atrium). Those with prevalent CVD at baseline and with inadequate ECGs were excluded from analysis; Cox-regression age- and multivariable-adjusted models were estimated. Results: In total, data on 8565 persons aged 45-69 years at baseline were analyzed. Among those, 145 (1.6%) subjects had AF at baseline and of those 100 subjects had no existing CVD. During the 13-year follow-up, there were 431 cases of CVD death (10.9%) in the cohort, among them 63% (n=272) were fatal coronary heart disease (CHD) and 23% (n=101) were fatal stroke (2.5%). In age-adjusted models, men with baseline AF had increased risk of CVD death (HR=5.76; 95%CI 3.88-8.55), fatal stroke (HR=6.26; 95%CI 2.96-13.22), and fatal CHD (HR=5.86; 95%CI 3.58-9.59). After adjusting for other risk factors, the increased risk remained for all CVD outcomes: 4.49 (95%CI 2.84-7.09) for CVD death, 3.62 (95%CI 1.46-8.96) for fatal stroke, and 4.95 (95%CI 2.81-8.70) for fatal CHD. In women, the age-adjusted HR for CVD death in women with baseline AF was 3.92 (95%CI 1.60-9.62) but in fully-adjusted models the HR was attenuated (HR=2.22; 95%CI 0.87-5.70). The numbers of deaths from CHD and stroke in women were too small for meaningful analyses. Conclusion: In this urban population-based cohort of subjects free from CVD at baseline, 11% of participants died from CVD death during 13 years follow-up. Men and women with baseline AF had approximately 4-fold increase in CVD mortality risk. The estimated CVD excess mortality risk associated with AF in this Russian cohort is consistent with findings from Western European and North American populations.